Scientific methods in the development of the agro-industrial complex of Kazakhstan ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses the development of the agro-industrial complex in the Republic of Kazakhstan, as well as the goals, features, stages of implementation of the sectoral program for the development of the agro-industrial complex for 2015-2023. The purpose of this article is to review the results of the development of the agro-industrial complex in the Republic of Kazakhstan. The object of study in the article is the agricultural sector of the Republic of Kazakhstan. The practical significance of the study is associated with the development of a new Program for the development of the agro-industrial complex of the Republic of Kazakhstan. The possibilities of creating favorable conditions for the formation of a fund of innovations and their development in the production of Kazakhstan are shown.
Keywords: agrarian economy; agribusiness; agricultural products; agricultural production; crop production; animal husbandry; mineral fertilizers; cotton; wool; forestry; fisheries